Definitions matter: detection rates and perinatal outcome for infants classified prenatally as having late fetal growth restriction using SMFM biometric vs ISUOG/Delphi consensus criteria. (1st March 2023) - Schreiber, V.; Hurst, C.; da Silva Costa, F.; Stoke, R.; Turner, J.; Kumar, S.
Abstract: Objectives: Fetal growth restriction (FGR) is often secondary to placental dysfunction and is suspected prenatally based on biometric or circulatory abnormalities detected on ultrasound. The aims of this study were to compare the screening performance of the Society for Maternal–Fetal Medicine (SMFM) biometric criteria (estimated fetal weight (EFW) or abdominal circumference (AC) < 10 th centile) with that of the International Society of Ultrasound in Obstetrics and Gynecology (ISUOG)‐endorsed Delphi consensus criteria for late FGR for delivery of a small‐for‐gestational‐age (SGA) infant at term, emergency Cesarean section (CS) for non‐reassuring fetal status (NRFS), perinatal mortality and composite severe neonatal morbidity. Methods: We classified retrospectively non‐anomalous singleton infants as having late FGR (diagnosed ≥ 32 weeks) according to SMFM and ISUOG/Delphi criteria in a cohort of women who had been referred to the Mater Mother's Hospital, Brisbane, Australia and who delivered at term between January 2014 and December 2020. The study outcomes were delivery of a SGA infant (birth weight (BW) < 10 th or < 3 rd centile), emergency CS for NRFS, perinatal mortality (defined as stillbirth or neonatal death within 28 days of a live birth) and a composite of severe neonatal morbidity. We assessed the screening performance of various ultrasound variables by calculating the sensitivity, specificity, positive (PPV) and negative (NPV) predictive values, false‐positive and false‐negative rates, positive likelihood ratio (LR+) and negative likelihood ratio. Results: The SMFM and ISUOG/Delphi consensus criteria collectively classified 1030 cases as having late FGR. Of these, 400 cases were classified by both SMFM and ISUOG/Delphi criteria, whilst 548 cases were classified using only SMFM criteria and 82 cases were classified only by ISUOG/Delphi criteria. Prenatal detection of late FGR by SMFM and ISUOG/Delphi criteria was associated with increased odds of delivery of an infant with BW < 10 th centile (SMFM: adjusted odds ratio (aOR), 133.0 (95% CI, 94.7–186.6); ISUOG/Delphi: aOR, 69.5 (95% CI, 49.1–98.2)) or BW < 3 rd centile (SMFM: aOR, 348.7 (95% CI, 242.6–501.2); ISUOG/Delphi: aOR, 215.4 (95% CI, 148.4–312.7)). Compared with the SMFM criteria, the ISUOG/Delphi criteria were associated with lower odds (aOR, 0.5 (95% CI, 0.3–0.8)) of predicting a SGA infant with BW < 10 th centile, but higher odds of predicting emergency CS for NRFS (aOR, 2.30 (95% CI, 1.14–4.66)) and composite neonatal morbidity (aOR, 1.22 (95% CI, 1.05–1.41)). Both SMFM and ISUOG/Delphi criteria were associated with high LR+, specificity, PPV and NPV for the prediction of infants with BW < 10 th and BW < 3 rd centile. However, both methods functioned much less efficiently for the prediction of composite severe neonatal morbidity or emergency CS for NRFS, with LR+ < 10. The SMFM biometric criteria alone, particularly AC < 3 rd centile, had the highest LR+ values for the prediction of perinatal mortality. Conclusion: Both the SMFM and ISUOG/Delphi criteria had strong screening potential for the detection of infants with BW < 10 th or < 3 rd centile but not for adverse neonatal outcome. © 2022 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology.